β-Correction Spectrophotometric Determination of Gallium with AlizarineRed S - Gao, Hong-Wen; Shi, Hong-Liano (Asian Journal of Chemistry, 2010)
The determination of gallium has been improved by β-correction spectrophotometry with alizarine red S (ARS). β-Correction spectrophotometry can eliminate completely the effect of excess ARS in its gallium colored solution to give out the real absorbance of Ga-ARS chelate. All of the analytical sensitivity, accuracy and precision were higher than those in the single wavelength method. By means of the β-correction principle the characteristic parameters of the chelate can be determined acceptably, Beer's law was obeyed over the concentration range 0-1.0 mg/L Ga and the detection limit of Ga is 0.015 mg/L. This method has been applied to the analysis of environmental materials with satisfactory results.